On Effect of Planar Scaling on Microstrip Patch Antenna Performance - Esmaeilkhah, A.; Ghobadi, C.; Nourinia, J.; Majidzadeh, M. (Advanced Electromagnetics, 2019)
This paper aims at investigating the effect of planar scaling on Microstrip patch antenna performance. To this end, nine antennas with different sizes are fabricated on the same FR4 substrate with thickness of 1mm with different scale factors. Results indicate some deviations between the obtained expected, simulated and measured resonant frequency which could be mainly due to the truncation error effect, and the SMA connector effect in the scaling process. All the influential factors are studied in detail through the paper. Detailed discussion on the scaling process and its effect on the antenna performance would be presented.